Псы войны. Пробуждение Ареса: роман / Г. Бир ; пер. О. И. Романова - Бир Грег (Фантастика, 2016)
Экземпляры: аб. (20170210) / Инвентарный номер: 53893 / Цена: / Сис.шифр: И(7Сое) / Авт.знак: Б 64 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)